2005
DOI: 10.1017/s0952836905006928
|View full text |Cite
|
Sign up to set email alerts
|

Limb joints kinematics and their relation to increasing speed in the guinea pig Cavia porcellus (Mammalia: Rodentia)

Abstract: The kinematics of each joint of the guinea pig Cavia porcellus were studied during the locomotor cycle at increasing speed by high-speed cinefluorography. The main objective was to reveal the functional specific features of these structural elements in each dynamic phase of the cycle and also which limb joints are important during the increase of animal speed. Most of the analysed angles in C. porcellus were affected as the speed increased, both in trot and gallop. However, only a few of them were correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Scapulae and forearms of two-toed sloths move in matched motion across the observed speed range. Kinematic values such as scapular touch-down and lift-off angles and excursions are highly similar to those reported for pronograde locomotion (Jenkins and Weijs, 1979;Fischer et al, 2002;Rocha-Barbosa et al, 2005), and are especially close to terrestrial mammals of similar size. Mean amplitude of scapular retraction is 34 • in two-toed sloths, 35 • in dogs, 41 • in goats and cats, and 28 • in vervet monkeys (Boczek-Funcke et al, 1996;Whitehead and Larson, 1994;Fischer and Blickhan, 2006).…”
Section: Conserved Kinematics and Consequences Of Limb Morphology Pecsupporting
confidence: 81%
See 1 more Smart Citation
“…Scapulae and forearms of two-toed sloths move in matched motion across the observed speed range. Kinematic values such as scapular touch-down and lift-off angles and excursions are highly similar to those reported for pronograde locomotion (Jenkins and Weijs, 1979;Fischer et al, 2002;Rocha-Barbosa et al, 2005), and are especially close to terrestrial mammals of similar size. Mean amplitude of scapular retraction is 34 • in two-toed sloths, 35 • in dogs, 41 • in goats and cats, and 28 • in vervet monkeys (Boczek-Funcke et al, 1996;Whitehead and Larson, 1994;Fischer and Blickhan, 2006).…”
Section: Conserved Kinematics and Consequences Of Limb Morphology Pecsupporting
confidence: 81%
“…We attribute the nevertheless high importance of the scapula for the generation of step length to the negative influence of hands on step length (see below), which in turn increases the importance of the remaining elements. Similarly, the kinematics of arm, elbow and forearm are strikingly similar to those of pronograde small mammals (Jenkins and Weijs, 1979;Fischer et al, 2002;Rocha-Barbosa et al, 2005), rhesus monkeys (Courtine et al, 2005), small arboreal primates (Schmidt, 2008), and dogs (Goslow et al, 1981). Two-toed sloth forelimb proportions resemble those of primates, especially those of advanced climbers such as lorises and colobines (Schmidt, 2008).…”
Section: Conserved Kinematics and Consequences Of Limb Morphology Pecmentioning
confidence: 89%
“…Across absolute and dimensionless speed, the largely invariant swing phase durations of the three charadriiforms agree with previous studies which have found this trait to be nearly constant with increasing speed during terrestrial locomotion of birds (Gatesy, 1999a;Reilly, 2000;Verstappen et al, 2000;Abourachid, 2001;van Coppenolle and Aerts, 2004;Rubenson et al, 2004;White et al, 2008;Nudds et al, 2010;Nyakatura et al, 2012;Stoessel and Fischer, 2012). The cost of swinging the limbs has been directly measured as being 26% of the total metabolic energy expended in running guinea fowl (Marsh et al, 2004); the invariant swing duration with increasing speed suggests that birds are limited in being able to more rapidly swing their limbs and thus rotational inertia of swinging limbs may be an important limiting factor in terrestrial locomotion (see also Rocha-Barbosa et al, 2005;Kilbourne, 2013;Hoffman, 2013, 2015).…”
Section: Discussion Temporal Traitsmentioning
confidence: 99%
“…Speed independency of limb kinematics has been shown for a tenfold range of speed in more than 300 strides for the pika (Fischer and Lehmann, 1998). In addition, speed independency of kinematic parameters was reported for the kowari and the gray short-tailed opossum (Kühnapfel, 1996), for the tree shrew (Schilling and Fischer, 1999), and for the guinea pig, a close relative of the cui (Rocha-Barbosa et al, 1996;Rocha-Barbosa et al, 2005). In particular, the detailed study on speed sensitivity of limb kinematics in the guinea pig showed that, although most joint angles were affected as speed increased, only a few angles were correlated to speed.…”
Section: Table·3 Continuedmentioning
confidence: 96%